Cousinia sharifii, a new species of Cousinia sect. Cynaroideae (Asteraceae) from NW Iran - Attar, Farideh; Rad, Mohammad Amini (Phytotaxa, 2019)
A new species of Cousinia (sect. Cynaroideae Bunge) is described and illustrated. Cousinia sharifii was found in mountain steppes near the border between Iran (W Azarbaijan) and Turkey. It is related to the complex of C. canescens s.l., in which it can be distinguished by the shape of involucre and phyllaries, and by the number of flowers and phyllaries. A distribution map, a line drawing and a scanned image of the type specimen of the new species are provided.